Rethinking Education Research methodologies-Dominance of Western perspectives? - Yu Sing Ong (Intelektual Pustaka Media Utama, 2016)
This paper examines the different approaches and methods in comparative education research. It begins with a broad overview of the influences of Western philosophies and how Western education researchers approach social situations. Its differences with Chinese philosophies were highlighted with the concept of dao and Confucianism. More than just an epistemological discussion, this paper argues that Western researchers’ biasness towards Asian researchers may be due to their failure or lack of experience in making the connections with Asian social systems. It attempts to provide some plausible explanations of the prevalence of biasness by peer reviewers of Western journals.